(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Auri A, Faridah E, Sumardi, Hardiwinoto S. 2021. The effect of crown pruning and induction of Acremonium sp. on agarwood formation in Gyrinops caudata in West Papua, Indonesia. Biodiversitas 22: 2604-2611. Agarwood-producing trees have been planted by the community, but have currently not produced agarwood resin. This research examines the crown pruning effect and fungi inoculation effectivity on the formation of agarwood resin in Gyrinops caudata. The environmental modification was also ascertained based on the real environmental situation in natural forests. Furthermore, it was assumed that environmental conditions significantly influenced the growth, G. caudata tree association, and fungi infection. This method involved the tree crown cover modification. Tree crown was categorized into three different classes, i.e. dense crown (no pruning); moderate (pruning 25%), and sparse (pruning 50%). The results showed that inoculating fungi of Acremonium sp. to infection coverage area after three months produced the best results, due to Fcount 79.671. However, crown prunings obtained through heavy, moderate and non-pruning did not show any effect on stem infection spread. In the sixth month, it was observed that the fungi inoculation factor of Acremonium sp. had a significant effect on infection spread formation by Fcount of 168.894. The change in wood internal tissue also had a highly significant effect as depicted by Fcount 461.516. The fragrance level treatment also showed a considerable effect with Fcount 290.385.